Dejatelʹnostʹ Russkoj Pravoslavnoj Cerkvi v postsovetskij period v Kazachstane = The role of the Russian Orthodox Church in the interreligious dialogue in Kazakhstan - Rysbekova, S. S. (Chabaršy. Dintanu serijasy, 2015)
The article analyzes the place and role of the Russian Orthodox Church in strengthening interfaith dialogue and its contribution to the development of Kazakhstan culturein the modern era. Its impact on public consciousness, as well as the contribution of the Russian Orthodox Church in the promotion of tolerance with other faiths in Kazakhstan. The article shows that the activities of the Russian Orthodox Church in Kazakhstan has its own traditions: to support all state and public institutions in pursuit of social harmony. The article shows that at the present stage the Russian Orthodox Church carries out the regulation of the relations with the state, with the believers of other religious organizations on the basis of international legal standards, domestic legislation and canonical norms.